Resistance of the Law to Technology: A Teubnian Analysis of Communication and Regulation - Chacon, Eduarda Moraes (Law, State and Telecommunications Review, 2018)
Purpose ”“ The article aims to confirm if there is resistance of the Law to Technology in order to admit the protagonism achieved by the second in the last years and to adjust the first to this new reality. Once confirmed the hypothesis, the purpose is to discuss how to overcome this resistance. Methodology/approach/design ”“ Review the works of Gunther Teubner, especially The Law as an Autopoietic System, in order to include Technology as a second-degree system, the same way that are Law, Economics and Politics. Findings ”“ Once is confirmed that the Technology was elevated to the category of a second-degree subsystem, the logic of the interaction between the other subsystems of the same classification will change and it will be demanded from Law the recognition of the new dynamics and its adjustment as to viabilize the communication as a mechanism of pre-regulation between itself and the Technology. Practical implications ”“ Given the confirmation of the hypothesis and the fact that the Law is not yet able to internalize a version of reality that includes the Technology in an effective way, the text explores in what ways this scenario can be changed so that lawyers and law enforcers will acquire the grammar they need, being no longer technological-illiterates. Originality/value ”“ This article is original because it reviews Teubner’s work on systems to add a new subsystem, Technology, while discusses the consequences of this change to the legal subsystem.